Anxiety disorder in academic situations among the adolescent school students of a few prominent schools in three districts of Bangladesh - Alam, Muhammad Shamsul; Binni, Subrina Yeasmin; Khan, Muhammad Zillur Rahman; Hossain, Zoha Mohammad Meherwar; Tasmia, Nur Taj Jarin; Tuba, Farah (Bangladesh Journal of Psychiatry, 2019)
Adolescence is a crucial period from academic perspective and anxiety in this period plays an important role in this respect. The objective of this study was to assess the level of anxiety among the adolescent school students in respect of gender, economic status of the families and some relevant factors. It was a cross-sectional study conducted in Dhaka, Chattogram and Rajshahi districts in some prominent schools. The respondents were 123 in number they were of class nine and ten and the range of age was from 14 to 17 years. The study period was from September 2016 to September 2017. The data were collected by using the questionnaire Achievement Anxiety Test developed by R. Alpert and R. Haber in 1960. The results showed that 71 respondents were boys and 52 were girls. It was found that 101 (82.12%) respondents were seriously anxious. There was no statistically significant difference of the occurrence of anxiety disorder among the boys and girls (p >0.05). The lower middle class of the society showed the highest occurrence of serious level of anxiety (59.4%) followed by respondents of the upper middle class having 27.8% adolescents having the same problem. Comparing with the other classes (i.e. the poor and the rich), the difference was statistically highly significant at p <0.001. The overall findings of this study indicated negative status of anxiety level among the respondents. Therefore, we should be aware in this respect and our families, educational institutions and concerned authorities including psychologists and psychiatrists should do the necessary actions. Bang J Psychiatry 2019; 33(2): 23-26